Fabriquer la tradition canadienne-française : le tabac canadien et la construction de l’identité canadienne-française, 1880-1950 - Rudy, Jarrett (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Tabac

The Goode House (The Westmount Historian, 2021)
Number: 2
Keywords: Conservation; Famille; Jardins; Patrimoine

Quand le temps s'arrête: une promenade dans le jardin de la maison Goode / Window to the Past: A Walk in the Garden of the Goode House - Adib, Danièle; Crépeau, Antoine (The Westmount Historian, 2021)
Number: 2
Keywords: Jardins

Au coeur de la contre-culture. La revue Mainmise et le cannabis, 1969-1973 - Brouillard, Marc-André (Cap-aux-Diamants, 2019)
issued: 2019-21-00

La Montagne vous appelle - Mathieu, Jocelyne (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)
Keywords: Femmes; Mont Royal; Patin; Raquetteurs; Ski; Vêtements

Les dessus et les dessous de la mode à Montréal - Back, Francis (Cap-aux-Diamants, 2017)
issued: 2017-22-00
Keywords: Vêtements

Politicking for Postwar Modernism: The Architectural Research Group of Ottawa and Montreal - Valen, Dustin (Urban History Review / Revue d'histoire urbaine, 2017)
issued: 2017-21-00

Un obscur projet de restauration de la noblesse (1897-1937) - Drolet, Yves (Cap-aux-Diamants, 2016)
issued: 2016-22-00
Keywords: Famille

L'appropriation de la culture punk: étude ethnographique du punk montréalais en 2015 - Lamarque, Julia (Université du Québec à Montréal, 2016)
Keywords: Musique

L'underground musical des années 1970 et l'émergence de la "musique actuelle" - Lefebvre, Marie-Thérèse (La contre-culture au Québec, 2016)
Keywords: Musicien; Musique

A Locational History of Fashion in Montréal - Sark, Katrina; Bélanger-Michaud, Sara Danièle (University of Chicago Press, 2016)
Keywords: Cinéma; Confection; Costume; Expositions; Musique; Musée McCord; Musée des Beaux-Arts; Musées; Vêtements

Conforme? Une histoire sociale du vêtement masculin chez les élites de Montréal, 1837-1918 - Villeneuve, Louis-Étienne (Université du Québec à Trois-Rivières, 2016)
Keywords: Bourgeoisie; Vêtements

Baptiste Ladébauche, du folklore au cabaret: à propos des collaborations d'Albéric Bourgeois et de Charles Marchand dans les années 1920 - Bellemare, Luc (Quand la caricature sort du journal: Baptiste Ladébauche, 1878-1957, 2015)
Keywords: Bourgeois; Albéric; Cabarets; Caricature; Chanson; Musique

De Montmartre à Broadway: le cabaret Au matou botté de Montréal (1929-1932) - Bellemare, Luc (Mens, 2015)
issued: 2015-23-00
Keywords: Cabarets; Cafés

Premiers regards sur les oeuvres d'art de la CSDM: Une histoire de commandes, de courants artistiques, de matérialités, d'intégrations - Doucet, Danielle (ARQ - Architecture Québec, 2015)
Number: 172

L'avènement du patrimoine et la construction de l'image touristique de Montréal - Oualid El Alaoui, Hind (Université du Québec à Montréal, 2015)
Keywords: Patrimoine; Tourisme

La danse pour tout un chacun: pratiques différenciées d’un loisir commercial à Montréal pendant l’entre-deux-guerres - Roquigny, Peggy (Mens, 2015)
issued: 2015-23-00
Keywords: Danse

Race and beauty in Canada: print culture, retail, and the transnational flow of products, images and ideologies, 1700s to present - Thompson, Cheryl (Université McGill, 2014)
Keywords: Esclaves; Noirs

Disunion City: The Fashion of Urban Youth in Montreal, Quebec - Woodhouse, Chelsea (Université de Montréal, 2013)
Keywords: Vêtements

Porosité des pratiques. Étanchéité du discours: réflexions sur l'analyse de la diffusion musicale radiophonique au Québec entre 1922 et 1939 - Lefebvre, Marie-Thérèse (Globe: revue internationale d'études québécoises, 2012)
Number: 1-2
Keywords: Musique; Radio

Fashioning Identity: The Hostesses of Expo 67 - Kirkman (Université Concordia, 2011)

La mode dans le quotidien des femmes: l'apport des magazines - Mathieu, Jocelyne (Les Cahiers des Dix, 2011)
Number: 65
Keywords: Femmes; Vêtements

Loisirs dansants de la bourgeoisie anglo-montréalaise. Transformation et persistance des lieux de pratique, 1870–1940 - Roquigny, Peggy (Urban History Review / Revue d'histoire urbaine, 2011)
issued: 2011-23-00
Keywords: Anglophones; Bourgeoisie; Danse

Andy Warhol at Expo 67: Pop In and Pop Out - Côté, Jean-François (Expo 67: Not Just a Souvenir, 2010)
Keywords: Expositions

Mainstreaming the Perception and Practice of Ethical Fashion in Montreal - Craven, Ryan John (Université Concordia, 2009)
Keywords: Vêtements

L'Osstidcho ou le désordre libérateur - Roy, Bruno (XYZ, 2008)
Keywords: Musique

"Bonnie Lassies" and a "Coat of Many Colours": Highland-Inspired Clothing at the McCord Museum - Stack, Eileen (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Musée McCord; Musées; Vêtements; Écossais

Design and Innovation in Montreal through the 1960s and the 1970s - Sharman, Lydia Ferrabee (Material History Review / Revue d’histoire de la culture matérielle, 2005)
issued: 2005-21-00
Keywords: Expositions; Place Ville-Marie; Transport en commun

Dicomode: dictionnaire de la mode au Québec de 1900 à nos jours - Baril, Gérald (Fides, 2004)
Keywords: Confection; Vêtements

Le mouvement Slow Food à Montréal: reflet d'une nouvelle conscience alimentaire cosmopolite - Bélanger, Esther (Université Concordia, 2004)
Keywords: Alimentation

Enduring Roots: Gibb and Co. and the Nineteenth-Century Tailoring Trade in Montreal - Cariou, Gail (Fashion. A Canadian Perspective, 2004)
Keywords: Confection; Vêtements

Dressing Up: A Consuming Passion - Cooper, Cynthia (Fashion. A Canadian Perspective, 2004)
Keywords: Vêtements

Fashion and Refuge: The Jane Harris Salon, Montreal, 1941-1961 - Ferrabee Sharman, Lydia (Fashion. A Canadian Perspective, 2004)
Keywords: Vêtements

Defrocking Dad: Masculinity and Dress in Montreal, 1700-1867 - Noel, Jan (Fashion. A Canadian Perspective, 2004)
Keywords: Papineau; Louis-Joseph; Ramezay; Claude de; Redpath; John; Vêtements

Fashion. A Canadian Perspective - Palmer, Alexandra (University of Toronto Press, 2004)
Keywords: Confection; Vêtements

The Association of Canadian Couturiers - Palmer, Alexandra (Fashion. A Canadian Perspective, 2004)
Keywords: Confection; Vêtements

Montreal's Fashion Mile: St Catherine Street, 1890-1930 - Sifton, Elizabeth (Fashion. A Canadian Perspective, 2004)
Keywords: Rues; Sainte-Catherine (rue); Vêtements

'Very Picturesque and Very Canadian': The Blanket Coat and Anglo-Canadian Identity in the Second Half of the Nineteenth Century - Stack, Eileen (Fashion. A Canadian Perspective, 2004)
Keywords: Anglophones; Vêtements

Mode, société et apparence: la mode féminine au Québec de 1945 à 2000 - Dulac, Françoise (Université Laval, 2003)
Keywords: Femmes; Vêtements

Créer en récupérant: les enjeux de la récupération des textiles dans le design de mode québécois depuis 1980 - Simard, Isabelle (Université Laval, 2002)
Keywords: Textile; Vêtements

Manly Smokes: Tobacco Consumption and the Construction of Identities in Industrial Montreal, 1888-1914 - Rudy, Robert Jarrett (Université McGill, 2001)
This dissertation explores the cultural practice of smoking and its connection to social relations from the beginning of cigarette mass production in Montreal in 1888 to the First World War. It uncovers the norms of smoking etiquette and taste, their roots in gender, class and race relations and their use in reproducing these power relationships. It argues that these prescriptions reflected and served to legitimize beliefs about inclusion, exclusion and hierarchy that were at the core of nineteenth century liberalism. Liberal ideals of self-control and rationality structured the ritual of smoking: from the purchase of tobacco; to who was to smoke; to how one was supposed to smoke; to where one smoked. These prescriptions served to normalize the exclusion of women from the definition of the liberal individual and to justify the subordination of the poor and cultural minorities. Furthermore, even while these prescriptions were at their height, an emergent group of beliefs began to recast notions of respectable smoking around new ideals of speed and ungendered universality. This challenge was not only part of the transition from bourgeois to mass consumption, it was the roots of a transformation of the liberal order in the years previous to the First World War.
Keywords: Tabac

A Little On the Wild Side: Eaton's Prestige Fashion Advertising Published in the Montreal Gazette, 1952-1972 - Bosnitch, Katherine (Université Concordia, 2000)
Keywords: Eaton; Magasins; Montreal Gazette; Publicité